(untitled) (World Bulletin of Public Health, 2025)
Esophageal atresia (AP) is one of the most severe malformations requiring emergency surgical treatment in the neonatal period. The frequency of occurrence is 1:3000-4500 live births. Despite significant advances in the surgical treatment of this pathology, mortality remains high and amounts to 15-50%, depending on concomitant malformations and birth weight.